2013
DOI: 10.1254/jphs.13167fp
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Vascular Concentration of Angiotensin II–Receptor Blockers on the Mechanism of Lowering Blood Pressure in Spontaneously Hypertensive Rats

Abstract: Abstract.To clarify the hypotensive mechanism of angiotensin II receptor-blockers (ARBs), drug concentrations in plasma and vascular tissues were measured using matrix-assisted laser desorption ionization time-of-flight mass spectrometry and imaging mass spectrometry. In spontaneously hypertensive rats, systolic blood pressure (SBP) was measured 2 and 24 h after administration of candesartan cilexetil (0.3, 1, or 3 mg/kg) or azilsartan (0.3, 1, or 3 mg/kg). SBP was similarly lowered 2 h after administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Among the many angiotensin receptor blockers (ARBs), azilsartan has been reported to be lipophilic and have a high affinity for tissues (18). Therefore, we used it to block the cardiac tissue angiotensin II AT1 receptor in SHRs.…”
Section: Protocol 1 (Effect Of Azilsartan)mentioning
confidence: 99%
“…Among the many angiotensin receptor blockers (ARBs), azilsartan has been reported to be lipophilic and have a high affinity for tissues (18). Therefore, we used it to block the cardiac tissue angiotensin II AT1 receptor in SHRs.…”
Section: Protocol 1 (Effect Of Azilsartan)mentioning
confidence: 99%
“…Azilsartan has a higher affinity for and slower dissociation from angiotensin II type 1 receptors than other ARBs 12 . Indeed, azilsartan exhibits 3.1 times higher affinity for arteries than candesartan even after a drug washout 13 . Our retrospective study showed that azilsartan improves LV diastolic dysfunction more than candesartan in patients with HF 14 , suggesting as well as inspiring us to prospectively evaluate azilsartan’s effects compared with candesartan on LV diastolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Among ARBs, azilsartan has been reported to show higher affinity for the angiotensin II type 1 (AT1) receptor [ 4 ] and better tissue penetration [ 5 , 6 ] compared to current agents, being the first drug to demonstrate statistically significant superiority in head-to-head comparison with another ARB [ 7 ].…”
Section: Introductionmentioning
confidence: 99%